Unusual manifestations of adrenal insufficiency: A case report of hypopituitarism and Well's syndrome after apoplexy of a silent pituitary gonadotropic adenoma. Issue 22 (3rd June 2022) - Hsu, Chia-Chen; Lin, Hong-Da; Huang, Chung-Yen; Chiang, Yi-Lun
Abstract: Rationale: Pituitary apoplexy occurs in about 8% of those with nonfunctioning pituitary adenoma. Subsequent hormone deficiency, especially corticotropic deficiency, is the most common finding. We describe the unusual manifestations of adrenal insufficiency that are usually overlooked in such cases, with the aim of raising awareness of this disease. Patient concerns: A 53-year-old male with a history of hyponatremia came to our hospital with intermittent fever and generalized pruritic skin rash. He also reported general weakness, abdominal pain, poor appetite, and severe retroorbital headache. Diagnoses: Laboratory data revealed hypereosinophilia, hypotonic hyponatremia, and hypopituitarism, including secondary adrenal insufficiency. Sellar magnetic resonance imaging revealed a pituitary macroadenoma, 2 cm in height, with mild displacement of the optic chiasm. Pathologic report and immunohistochemical stains of surgical specimen showed pituitary gonadotropic adenoma with apoplexy. Interventions: Transsphenoidal removal of the pituitary adenoma was performed. The patient received intravenous hydrocortisone then oral form cortisone acetate regularly. Outcomes: His symptoms and laboratory data recovered after the operation and medical treatment. Lessons: This case highlights that eosinophilia, pruritic skin rash and fever can be manifestations of adrenal insufficiency, and that they may initially be regarded as cellulitis.